Association of Interleukin-17 gene polymorphisms with susceptibility to chronic hepatitis B virus infection and clearance in Iranian population. (July 2020) - Tayefinasrabadi, Hamideh; Mohebbi, Seyed Reza; Hosseini, Seyed Masoud; Azimzadeh, Pedram; Pourhoseingholi, Mohamad Amin; Ghaemi, Amir; Sharifian, Afsaneh; Asadzadeh Aghdaei, Hamid; Zali, Mohammad Reza
Abstract: Hepatitis B virus (HBV) approximately infects 350 million people. Interleukin-17 (IL-17) as a pro-inflammatory cytokine, have been found to modulate the immune system in infectious and inflammatory diseases. Recently, the influence of genetic changes like single nucleotide polymorphisms (SNP) on expression rate and function of cytokine has been widely investigated. This study was performed to determine any possible association between four IL-17 SNPs (rs2397084, rs763780, rs2275913 and rs10484879) and chronic HBV infection. A total of 466 samples were recruited and studied including 199 chronic patients, 172 healthy controls and 95 spontaneous clearance individuals between genotype and allele frequencies. Genomic DNA was extracted from peripheral blood cells and Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) was used to determine the SNPs genotypes. Genotypes frequencies for rs10484879 were 63.8% CC, 31.7% AC, 4.5% AA in chronic group, 54.7% CC, 36.6% AC, 8.7% AA in control and 63.2% CC, 33.7% AC, 5.8% AA in cleared samples. The AC genotype for rs10484879 was significantly associated with a decreased risk of HBV chronicity (Pvalue = 0.031, OR = 2.699, 95%CI: 1.097–6.639). The genotype and allele frequencies of rs2397084, rs763780 and rs2275913 did not show significant difference between chronic HBV patients and healthy controls. Indeed, there is no significant difference between clearance and chronic patient's genotypes in four SNPs. Our results suggest that IL-17A rs10484879 single nucleotide polymorphism genotype is probably associated with susceptibility to HBV chronic infection, while no significant differences in IL-17 rs2397084, rs763780 and rs227591 distribution were found between HBV patients and spontaneous clearance individuals and control participants. Highlights: The AC genotype for IL-17 rs10484879 single nucleotide polymorphism was associated with a decreased risk of HBV chronicity. The genotype and allele frequencies of rs2397084, rs763780 and rs2275913 did not show significant difference between chronic HBV patients and healthy controls. In addition, there is no significant difference between clearance and chronic patient's genotypes in these four SNPs. Although the most frequent haplotype for these IL17 single nucleotide polymorphisms was TTGC in both CHB patients and controls group, none of the haplotypes showed any association with chronic hepatitis B.